Cover Feature: Synthesis and Characterization of Nanotubes from Misfit (LnS)1+yTaS2 (Ln=Pr, Sm, Gd, Yb) Compounds (Chem. Eur. J. 44/2018). Issue 44 (16th July 2018) - Serra, Marco; Stolovas, Dalit; Houben, Lothar; Popovitz‐Biro, Ronit; Pinkas, Iddo; Kampmann, Felix; Maultzsch, Janina; Joselevich, Ernesto; Tenne, Reshef
Abstract : Nanotubes from misfit layered compounds are grown by a chemical vapor transport process with TaCl5 as catalyst (growth promoter). Chlorine atoms bind to the solid crystallites in the hot zone and shuttle them to the cold zone where they grow to become LaS‐TaS2 nanotubes, releasing the chlorine atoms, which shuttle back to the hot zone. A SEM picture of the nanotubes appears in the background. More information can be found in the Full Paper by R. Tenne et al.on page 11354 .